2014
DOI: 10.1155/2014/314704
|View full text |Cite
|
Sign up to set email alerts
|

Antiphospholipid Antibodies in Women Undergoing In Vitro Fertilization Treatment: Clinical Value of IgA Anti-β2glycoprotein I Antibodies Determination

Abstract: Implantation failure could be related to antiphospholipid antibodies (aPL). We retrospectively analyzed the usefulness of aPL determination in women undergoing IVF. Conventional aPL of the antiphospholipid syndrome, lupus anticoagulant (LA), anticardiolipin antibodies (aCL), anti-β2glycoprotein I (aβ2GPI) antibodies, and IgG and IgM isotypes as well as IgA isotype were analyzed in women presenting with at least two implantation failures after in vitro fertilization (IVF). In a population of 40 IVF patients, a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 16 publications
0
18
0
Order By: Relevance
“…This result was associated with important heterogeneity across studies and was not confirmed in considering only cohort studies, which could, however, depend on Type II error. Considering IgA isotypes (not actually included in APS Sydney criteria), similar frequency was noted in 2790 patients with recurrent miscarriage/implantation failure vs controls, but in 40 patients undergoing IVF Paulmyer‐Lacroix et al found that only IgA anti‐β2GPI antibodies prevalence was significantly different from controls (5/40; 12.5% vs 1/100; 1%). Nevertheless, as functional effects are determined by the immunoglobulins’ Fc fragment, the clinical significance of such antigen binding assay (Fab fragment binding) need to be determined.…”
Section: Autoantibodies In Urm and Rifmentioning
confidence: 71%
“…This result was associated with important heterogeneity across studies and was not confirmed in considering only cohort studies, which could, however, depend on Type II error. Considering IgA isotypes (not actually included in APS Sydney criteria), similar frequency was noted in 2790 patients with recurrent miscarriage/implantation failure vs controls, but in 40 patients undergoing IVF Paulmyer‐Lacroix et al found that only IgA anti‐β2GPI antibodies prevalence was significantly different from controls (5/40; 12.5% vs 1/100; 1%). Nevertheless, as functional effects are determined by the immunoglobulins’ Fc fragment, the clinical significance of such antigen binding assay (Fab fragment binding) need to be determined.…”
Section: Autoantibodies In Urm and Rifmentioning
confidence: 71%
“…However, neither the indication for APA screening was mentioned nor the cut-off levels for APA positivity conformed international consensus criteria in these two studies. A third study reporting a positive association between APA and ART outcome included only eight women who tested positive for anticardiolipin antibody after failing two ART cycles and 32 women without anticardiolipin antibodies as controls [26]. While the Sapporo criteria APAs were not found to affect ART outcome, antibeta2 microglobulin IgA antibody positivity (defined as >99th percentile) was found to be detrimental.…”
Section: Acquired Thrombophilia and Assisted Reproductive Technologiesmentioning
confidence: 99%
“…Data published so far on immunoglobulin levels were mostly based on small patient numbers. Fertility patients with antiphospholipid syndrome showed higher concentrations of immunoglobulin G and M [59] as well as immunoglobulin A [60] than patients with normal fertility.…”
Section: Discussionmentioning
confidence: 86%